VD_FINDINFO Arrêt / 2021 / 856 vom 28. September 2021 - VD Tribunal cantonal (2021)
APTITUDE AU PLACEMENT, AUTORISATION DE TRAVAIL | 15 al. 1 LACI, 8 al. 1 LACI, 54 OASA, 11 al. 1 LEI, 21 al. 1 LEI, 23 LEI